2017
DOI: 10.1002/2016jb013132
|View full text |Cite
|
Sign up to set email alerts
|

Slip‐behavior transitions of a heterogeneous linear fault

Abstract: Geological faults have frictional heterogeneity. Here we investigate the slip behavior of such heterogeneous faults in the simplest situation, simulating antiplane shear slip along an infinite linear fault in a 2‐D elastic model space, subjected to constant loading by external stresses characterized by stiffness and plate‐motion velocity. The fault is discretized into many subfaults, each of which has either a velocity‐weakening (VW) or velocity‐strengthening (VS) friction law. We vary the proportion of the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 57 publications
8
35
0
Order By: Relevance
“…Consistent with previous studies (e.g., Skarbek et al 2012;Dublanchet et al 2013;Luo and Ampuero 2017;Yabe and Ide 2017), we observed several different types of slip behavior in our parameter studies. The first is the "total seismic" regime, in which a mainshock event ruptures the entire seismogenic zone on the fault (parameter sets A-C in Fig.…”
Section: Seismic Cyclesupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous studies (e.g., Skarbek et al 2012;Dublanchet et al 2013;Luo and Ampuero 2017;Yabe and Ide 2017), we observed several different types of slip behavior in our parameter studies. The first is the "total seismic" regime, in which a mainshock event ruptures the entire seismogenic zone on the fault (parameter sets A-C in Fig.…”
Section: Seismic Cyclesupporting
confidence: 93%
“…They reported a variety of slip behaviors, from seismic slip that ruptures only the velocity-weakening zone (VWZ) to seismic slip that ruptures the entire fault, including both the VWZ and velocity-strengthening zone (VSZ). Yabe and Ide (2017) documented slower deformation at the transition between two behaviors, which may correspond to slow earthquakes. In contrast, Skarbek et al (2012) documented transitions from seismic to slow slip on a finite frictionally heterogeneous fault.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We exclude simultaneous slip of the two regions (e.g. Dublanchet et al 2013;Yabe and Ide 2017), even though it could be easily treated by models describing the dynamics of faults with two asperities (e.g. Dragoni and Santini 2015;Dragoni and Tallarico 2016).…”
Section: The Modelmentioning
confidence: 99%
“…Kato (2004Kato ( , 2014 discussed the interplay between velocity-weakening and velocitystrengthening patches on a fault plane and the conditions for seismic and aseismic slip events. Dublanchet et al (2013) and Yabe and Ide (2017) considered a fault with a large number of asperities and pointed out that asperity concentration remarkably affects the slip behaviour of heterogeneous faults containing both velocity-weakening and velocity-strengthening regions: specifically, the entire fault may slip seismically if the asperity concentration exceeds a critical threshold. Bulk relaxation of the crust and the effect of pore fluid diffusion may also play a role.…”
Section: Introductionmentioning
confidence: 99%